Kajian pengembangan kendaraan listrik di Indonesia: prospek dan hambatannya - Tulus Pangapoi Sidabutar, Victor (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
The transportation sector is now starting to shift from using fossil fuels to electricity that is more environmentally friendly because this sector contributes the most greenhouse gas emissions. The development of the use of electric vehicles is growing rapidly with the largest market is China followed by Europe and the United States. The development of electric vehicles is very dependent on the policies issued by the country. Indonesia desires to be one of the centers of the world's electric vehicle industry and for that, it must pay attention to challenges in terms of cost, standards, power generation, incentive assistance, communication security, and a framework for integration. In addition to this, if Indonesia wants to attract investors, it must pay attention to infrastructure readiness, ease of doing business, government policies, and research and development.